2016
DOI: 10.1128/iai.00705-16
|View full text |Cite
|
Sign up to set email alerts
|

Protein Malnutrition Impairs Intestinal Epithelial Cell Turnover, a Potential Mechanism of Increased Cryptosporidiosis in a Murine Model

Abstract: Malnutrition and cryptosporidiosis form a vicious cycle and lead to acute and long-term growth impairment in children from developing countries. Insights into mechanisms underlying the vicious cycle will help to design rational therapies to mitigate this infection. We tested the effect of short-term protein malnutrition on Cryptosporidium parvum infection in a murine model by examining stool shedding, tissue burden, and histologic change and explored the mechanism underlying the interaction between malnutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 38 publications
6
46
0
Order By: Relevance
“…If malnutrition leads to villous blunting and thus poor absorption, does the resultant malabsorption then foster further malnutrition, or is there a limit to the dysfunction one can accrue? Recently, Liu et al [39] demonstrated that even short-term protein malnutrition can lead to decreased weight gain, increased pathogen burdens and stifled epithelial cell proliferation in a murine model of Cryptosporidium parvum infection. Although C. parvum and C. jejuni infections differ greatly in their pathogenesis and rates of occurrence per location, the conclusion of this study is that diet plays a major role in the body’s ability to initiate repair mechanisms even after abbreviated periods of protein malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…If malnutrition leads to villous blunting and thus poor absorption, does the resultant malabsorption then foster further malnutrition, or is there a limit to the dysfunction one can accrue? Recently, Liu et al [39] demonstrated that even short-term protein malnutrition can lead to decreased weight gain, increased pathogen burdens and stifled epithelial cell proliferation in a murine model of Cryptosporidium parvum infection. Although C. parvum and C. jejuni infections differ greatly in their pathogenesis and rates of occurrence per location, the conclusion of this study is that diet plays a major role in the body’s ability to initiate repair mechanisms even after abbreviated periods of protein malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…68,69 Cryptosporidial infection in the setting of protein deficiency also caused impaired turnover of infected epithelial cells. 70 Similar synergies with protein or zinc deficiency were seen with EAEC infections. 7173 Conversely, murine rotavirus infections were less severe in undernourished conditions, 74 which may be because the intestinal villi were blunted and less efficiently provided the lactase needed to “uncoat” the virus as part of pathogenesis.…”
Section: Current Definitionsmentioning
confidence: 83%
“…Furthermore, field and lab model studies can identify hypotheses to be tested in other study designs and raise potential interventions worthy of testing. For example, the impairment of cell turnover with protein deficiency that greatly increases the intensity and severity of cryptosporidial infection noted above 70 raises the possibility that intestinal repair nutrients like glutamine or citrulline might reduce the impaired growth and development seen with this infection in clinical studies.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various Cryptosporidium species are recognized weeks [17,18]. A protective role of the gut microbiota against cryptosporidiosis was also observed in neonatal mice [19,20] A protein-deficient diet was also found to increase susceptibility of mice to C. parvum [21]. This phenotype was attributed to a reduced epithelial cell turnover.…”
Section: Introductionmentioning
confidence: 95%